Integrated Entrepreneurship Guidance for Students of Al-Furqon Bondowoso Vocational School in Creating Productive and Independent Young Entrepreneurs - fawaid, fawaid; Saini, Saini; Khoir, Qoidul; Shiddiqi, Hasbi Ash; Miftahussurur, Wildan (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This study addresses the low entrepreneurial readiness among vocational education students, a condition that persists despite the increasing national demand for young entrepreneurs. This gap is evident in the lack of practical skills such as identifying business opportunities, calculating production costs, and effectively marketing products. The aim of this study was to strengthen students' entrepreneurial capacity through an integrated mentoring model tailored to their learning context at SMK Al-Furqon Bondowoso, Indonesia. The method used was a community-based training approach that included seminars, workshops, coaching, and hands-on practice during a three-day intervention (January 4-6, 2026). The findings indicate an increased understanding of entrepreneurial concepts, competency in calculating production costs, pricing, and profit margins, and improvements in designing basic marketing strategies using offline and online media. Participants also demonstrated a shift in attitudes toward entrepreneurship as a viable career path that can be planned as early as possible. The study concludes that context-responsive mentoring can bridge the gap between theoretical knowledge and practical application in vocational settings and has the potential to be replicated to support entrepreneurship development in similar institutions at the secondary education level. These findings also emphasize the importance of an entrepreneurial empowerment model for the younger generation.